The Most Famous Writer of the Low Countries: Herman Brusselmans Star Author and (Reluctant) Public Intellectual - Honings, Rick (Werkwinkel, 2017)
The Flemish writer Herman Brusselmans is the most famous author of the Low Countries. In this article, Herman Brusselmans is analysed as a star author. First and foremost, two striking aspects of Brusselmans’s stardom are analysed: his public visibility and the cult of the private. Attention is then focused on Brusselmans’s experience of celebrity, which he – like many other star authors – thematises in his books. Doing so, he consciously places himself in the context of popular culture. On the other hand, as a result of his celebrity status he has been expected – particularly in the last few years – to assume the role of public intellectual willy-nilly, and this in turn has had consequences for his work.